Social Media and Sustainable Fashion : Mediating Roles of Awareness and Attitude Among Young Indian Consumers - Uprety, Minal; Barik, Pratibha; Nim, Dheeraj (Prabandhan: Indian Journal of Management, 2025)
Purpose : This paper aimed to examine the mediating effect of awareness and attitude between social media platforms (SMP) and purchase intention of young consumers toward sustainable fashionable products. Methodology : A survey was conducted to collect data using a self-structured questionnaire among young consumers of India using convenience sampling. The hypotheses framed were tested from the collected data through the questionnaire filled out by 332 users of SMP. The measurement model was tested through the structural equation modeling technique with smart partial least square 2.0 software for assessing the impact of drivers of SMP on their credibility, awareness, attitude of young consumers, and their purchase intention. Findings : The results indicated that SMP had a significant positive influence on awareness and attitude toward sustainable fashion products (SFP). The analysis also demonstrated that awareness and attitude had a significant impact on purchase intention toward SFP, but attitude did not mediate the relationship between SMP and purchase intention; whereas, awareness had a significant partial mediating effect. Implications : The study is relevant for the marketers of SFP; they can use the obtained results to improve various drivers of SMP to create awareness, attract new customers, and to retain existing customers. Government organizations and policymakers could develop policies toward environmentally friendly products using the results. Originality : This study explored the influence of SMP on purchase intention and the mediating impact of attitude and awareness between SMP and purchase intention in the context of fashion products in India.